Generational Diversity in the Workplace: Psychological Empowerment and Flexibility in Spanish Companies - Sobrino-De Toro, Ignacio; Labrador-Fernández, Jesús; De Nicolás, Víctor L. (Frontiers in Psychology, 2019)
Intergenerational diversity is a universal fact in sustainability and today’s work environment. Current studies seek to find differences that exist between these generational groups that coexist, cooperate, and sometimes compete in business organizations. Sixteen focus groups have taken place, four for each generation to find the differences that may exist depending on that group membership. Specifically, the psychological empowerment and psychological flexibility variables have been analyzed, which have already shown their relevance to improve performance. Results show differences between the older generations (BB and Gen X) and the younger ones (Gen Y and Gen Z).